Is reputational risk important for bank performance? Evidence from CEE-11 countries - Miklaszewska, Ewa; Kil, Krzysztof; Pawłowska, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The 2007-2009 revealed the weaknesses of the growth foundation and failure of risk management systems in large global banks. Consequently, there has been renewed interest in the creation of stable and functional risk culture. Protecting a financial institution’s reputation is among the most significant challenges facing financial firms. Thus the aim of this paper is to analyze why reputational risk is important for banks, and to trace its sources and consequences. In the empirical part, the paper proposes a new method to measure reputational risk: Stakeholder Reputation Score (SRS). The panel regression models are used to examine the impact of the SRS indicator on bank performance, for listed banks in the CEE-11. The estimation results indicate that the efforts to enhance bank reputation may not have a positive effect on bank performance, which may explain why many banks deal with reputational risk mainly in the context of minimizing loss after a scandal, rather than treating it as a strategic, long-term goal
Argumenta Oeconomica, 2020, Nr 2 (45), s. 31-51
Keywords: reputational risk; Bank efficiency; banks in CEE